A new two-step modeling strategy for random micro-fiber reinforced composites with consideration of primary pores. (8th February 2022) - Cai, Heng; Ye, Junjie; Shi, Jinwang; Wang, Yiwei; Shi, Yang; Huang, Bo; Xu, Yonghe; Saafi, Mohamed; Ye, Jianqiao
Abstract: This paper presents a novel procedure to evaluate mechanical properties of random micro-fiber reinforced composites with consideration of primary pores. To this end, micro-CT experiment is conducted first to detect micro-scale morphology of the constituent materials, including size of pores and arrangement of fibers, etc. On this basis, a two-step modeling strategy with consideration of primary pores is proposed. In the first step, the equivalent mechanical properties of the pore defects and the micro-fibers are determined by the 3D parametric finite volume directly averaging micromechanics (FVDAM), by which an equivalent ellipsoidal reinforcing phase composed of fibers and pores is constructed. In the second step, the equivalent pores and fibers are embedded into matrix materials to build an RVE of the composite to calculate the elastic modulus of the composite. In addition, the 3D parametric FVDAM is further extended to simulate plastic deformation of PEEK matrix under quasi-static tensile loading. The results obtained from the proposed two-step modeling strategy have a good agreement with the results from experiments. Graphical abstract: This paper presents a novel method to evaluate mechanical proper ties of random micro-fiber reinforced composites with consideration of primary pores. To this end, micro-CT experiment is conducted to detect microscale morphology of the composites, including the size of pores and the arrangement of micro-fiber, etc. On this basis, a two-step modeling strategy with consideration of primary pores is proposed. Image 1